2007
DOI: 10.1016/j.abb.2006.11.014
|View full text |Cite
|
Sign up to set email alerts
|

Role of sphingomyelin and ceramide in the regulation of the activity and fatty acid specificity of group V secretory phospholipase A2

Abstract: We previously showed that group V secretory phospholipase A 2 (sPLA 2 V) is inhibited by sphingomyelin (SM), but activated by ceramide. Here we investigated the effect of sphingolipid structure on the activity and acyl specificity of sPLA 2 V. Degradation of HDL SM to ceramide, but not to ceramide phosphate, stimulated the activity by 6-fold, with the release of all unsaturated fatty acids being affected equally. Ceramide-enrichment of HDL similarly stimulated the release of unsaturated fatty acids. Incorporat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 39 publications
(65 reference statements)
3
16
1
Order By: Relevance
“…Treatment with DTT or TEAPC, general inhibitors of secretory PLA 2 s, decreased the DMB-mC11S (GS13)-and DMB-mC9S (GS20)-induced release of AA (Table 3). It is reported that ceramide activated secretory PLA 2 s including types IIa, V, and X, and the enzymes with ceramide prefer AA-containing phospholipids (19,20). Under our conditions with type III secretory PLA 2 from bee venom, however, we could not detect direct activation of the enzyme by DMB-mC11S (GS13).…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…Treatment with DTT or TEAPC, general inhibitors of secretory PLA 2 s, decreased the DMB-mC11S (GS13)-and DMB-mC9S (GS20)-induced release of AA (Table 3). It is reported that ceramide activated secretory PLA 2 s including types IIa, V, and X, and the enzymes with ceramide prefer AA-containing phospholipids (19,20). Under our conditions with type III secretory PLA 2 from bee venom, however, we could not detect direct activation of the enzyme by DMB-mC11S (GS13).…”
Section: Discussioncontrasting
confidence: 64%
“…Ca 2+ -independent PLA 2 (β-isofrom) is reported to participate in endoplasmic reticulum stress-induced apoptosis in insulinoma cells (36) and in macrophages (34). Secretory PLA 2 s play important roles in cell damage under pathological conditions including inflammation and atherogeneis (14,16,20). These findings including our data suggest the cytotoxicity induced by AA.…”
Section: Possible Role Of Release Of Aa In Cell Deathsupporting
confidence: 59%
See 1 more Smart Citation
“…Subbaiah and Liu ( 25 ) reported that lecithin-cholesterol acyltransferase, a specialized phospholipase A responsible for the esterifi cation of cholesterol in plasma, was inhibited by SM. The activities of lipoprotein lipase and secretory PLA2 have also been shown to be inhibited by SM in vitro (26)(27)(28)(29)(30). Dawson et al ( 31 ) reported that diacylglycerol-stimulated intracellular phospholipases were strongly inhibited by SM.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibitory effect of added SM upon enzyme activity was relieved by the addition of free cholesterol (FC) (14). Similarly, addition of SM/ceramide to PtdCho liposomes (3,15) showed a clear preference for release of arachidonate by group X sPLA 2 , although at reduced activity, whereas the addition of SM to the group V sPLA 2 digestion mixture inhibited the release of arachidonate (16), resulting in greater release of linoleate.…”
mentioning
confidence: 99%